Strategy of Implementing the Talaqqi Method in Learning the Memory of Al- Quran at SMP Muhammadiyah 57 Medan - Purba, Nurul Huda; Hasan, Ibrahim (Jurnal Ilmiah Global Education, 2025)
This research aims to find out: 1). Concept of strategy for applying the talaqi method in learning tahfiz Al Qur'an at SMP Muhammadiyah 57 Medan.. 2). Strategy for applying the talaqi method in learning tahfiz Al Qur'an applied at SMP Muhammadiyah 57 Medan 3). Factors influencing the strategy for implementing the talaqi method in learning tahfiz Al Qur'an at SMP Muhammadiyah 57 Medan with a focus on the strategy for implementing the talaqi method in learning tahfiz al Qur'an at SMP Muhammadiyah 57 Medan. Through tests, interviews and documentation studies conducted for 20 days (19 May to 10 June 2025), it was found that SMP Muhammadiyah 57 Medan had implemented the tahfiz Al Learning program Qur'an to increase students' religiosity, especially memorizing certain verses in the Qur'an. through the application of the talaqi method with a monotonous strategy, namely memorizing, depositing verses evaluated including memorization, makhraj and tajwid. This study uses a descriptive qualitative approach with interview methods, observations, and document studies to explore in-depth information about the application of the talaqi method of learning tahfiz Al Qur'an The results of the study indicate that the strategy for implementing the talaqi method that was 1). The concept of the talaqi method implementation strategy in learning to memorize the Qur'an at SMP Muhammadiyah 57 Medan involves the principal, tahfiz teachers and students themselves actively, 2). The strategy of implementing the talaqi method in learning to memorize the Qur'an applied at SMP Muhammadiyah 57 Measn has planning, learning activities and evaluation, 3). Factors that influence the strategy of implementing the talaqi method in learning to memorize the Qur'an at SMP Muhammadiyah 57 Medan have 2 factors, namely supporting factors and inhibiting factors.